2017
DOI: 10.5858/arpa.2016-0580-oa
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Immunohistochemistry Assay for Detection of CD155, the Poliovirus Receptor, in Malignant Gliomas

Abstract: Context. The oncolytic polio-rhinovirus recombinant (PVSRIPO) has demonstrated promise in currently ongoing phase I/II clinical trials against recurrent glioblastoma and was granted breakthrough therapy designation by the Food and Drug Administration/Center for Biologics Evaluation and Research. A reliable clinical assay to document expression of the poliovirus receptor, CD155, in routinely available patient tumor samples is needed for continued clinical development of PVSRIPO oncolytic immunotherapy in primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…These reservoirs for poliovirus propagation coincide with CD155 expression (9, 10). Poliovirus propagation in the gastrointestinal tract does not produce overt enteric pathology and is generally clinically silent; tropism for lower motor neurons is the reason for the pathognomonic signature of poliovirus -paralytic poliomyelitis- and an obvious grave concern for biosafety considerations.…”
Section: Safety Of the Recombinant Polio:rhinovirus Chimera Pvsripomentioning
confidence: 89%
See 2 more Smart Citations
“…These reservoirs for poliovirus propagation coincide with CD155 expression (9, 10). Poliovirus propagation in the gastrointestinal tract does not produce overt enteric pathology and is generally clinically silent; tropism for lower motor neurons is the reason for the pathognomonic signature of poliovirus -paralytic poliomyelitis- and an obvious grave concern for biosafety considerations.…”
Section: Safety Of the Recombinant Polio:rhinovirus Chimera Pvsripomentioning
confidence: 89%
“…CD155 expression is high in virtually all solid neoplasias (4), except Burkitt lymphoma, where CD155 is transcriptionally silenced, possibly due to Epstein Barr virus infection (43). We recently described validation of an immunohistochemistry protocol for reliable detection of CD155 expression in formaldehyde-fixed, paraffin-embedded tumor tissue sections [in glioblastoma; (9)]. Utilization of this assay in 19 samples of triple-negative breast cancer is shown in Figure 1.…”
Section: Targeting the Cd155 Immune Checkpointmentioning
confidence: 99%
See 1 more Smart Citation
“…10 PVSRIPO tropism is determined by CD155, 11 a high-affinity ligand for the T-cell immunoreceptor with immunoglobulin and immunoreceptor tyrosine-based inhibition motif domains. 12 In solid tumors, CD155 is broadly up-regulated on malignant cells 13,14 and expressed in antigen-presenting cells. PVSRIPO infection of neoplastic cells in vitro results in lethal cytotoxic effects and activates innate antiviral interferon responses.…”
mentioning
confidence: 99%
“…It should be reported that once recurrent, the median survival is only 4-7 months. 15,16 As cancer cells evolve to a totally malignant pattern and metastatic phenotype, they acquire multiple mutations and epigenetic modifications, creating a heterogeneous environment, resistant to standard treatment and frequently induce development in treatment refractory disease. Therefore, one of the challenges facing the cancer research community is to develop strategies that can combine and overcome the resistance mechanisms of the tumor.…”
Section: Zika's Infectionmentioning
confidence: 99%